ANALISIS TINGKAT MATHEMATICS ANXIETY DITINJAU DARI TINGKAT KEPERCAYAAN DIRI SISWA - Firda Mitha Andini; Maman Fathurrohman; Hepsi Nindiasari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Mathematics anxiety is one of the problems that affects students' learning performance, especially for students with a certain level of self-confidence. To find out, this study aims to analyze the level of mathematics anxiety viewed from students' confidence levels. This research uses a quantitative descriptive approach with a questionnaire as the data collection technique. The research was conducted in class X-4 at SMAN 1 Jawilan with 34 student respondents. The data were analyzed using descriptive statistics in the form of frequency distribution and level categorization. The research results show that the average level of low mathematics anxiety is possessed by 5 students (14.7%), the average level of moderate mathematics anxiety is possessed by 23 students (64.7%), and the average level of high mathematics anxiety is possessed by 6 students (20.4%). Meanwhile, the results of student self-confidence levels show that the average level of low self-confidence is possessed by 5 students (8.82%), the average level of high self-confidence is possessed by students (82.85%), and the average level of mild/low mathematics anxiety possessed by students is 8.82%. Student self-confidence level has a positive effect on controlling anxiety in class X 4 students of SMAN 1 Jawilan.